(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study dealt with the filing of the arbitration award, its substantive and formal conditions, as well as its purpose. It also analyzed the provisions of the Saudi arbitration law and judicial applications, comparing them with the provisions of Egyptian Arbitration law and their specific judicial applications. The study aimed to understand the procedures for filing arbitration award, the actions arbitration tribunals must take after issuing arbitration award, the legal nature of the filing procedures, who bears the responsibility for filing arbitration award, and the arbitration tribunal’s liability in case of non-compliance with filing procedures. It also sought to explore the consequences of filing arbitration award. The study found several key findings: Saudi regulations do not stipulate penalties for failing to file the arbitration award. Saudi regulations excel in specifying a period for filing arbitration award, which the tribunal is responsible for after issuing the award. Egyptian regulations excel in imposing the responsibility for filing arbitration award on the interested party, unlike Saudi regulations where this responsibility lies with the arbitration tribunal. The legal nature of filing arbitration award is regulatory and does not affect the arbitration process or invalidate its outcomes. The study concluded with several recommendations, the most important of which include: amending Article (44) of the Saudi Arbitration Law to transfer the responsibility of filing arbitration award to the interested party instead of the arbitration tribunal, and changing the currently used filing procedure, which involves filing a lawsuit, due to its inconsistency with the nature of the lawsuit.